Promotional strategies practiced by Amanah Saham Nasional Berhad (ASNB) and its impacts on investment decision / Nurhanisah Hamdan - Hamdan, Nurhanisah (Faculty of Business and Management, 2010)
Every single company needs strategies in order to survive or to become a leader in the market. Therefore a study towards the promotional strategies that gives impact towards investment decision and the strategies most suitable for the company has been carried out. The purpose of the study was to determine the overall levels perception customer, relationship between investment decision and promotional strategies and promotional strategies that gives the most impacts towards investment decision in the company. This study will take the Amanah Saham Nasional Berhad (ASNB), a unit trust company that involve in fully service environment as the pilot organization to be examine and evaluate. After the conclusion has been made, a few recommendations and suggestions were brought up that might be useful for future improvement of the company itself.